Plasma alkaline phosphatase polymer phism and it’s association with productivity in Iraqi fowl (Baghdad Science Journal, 2008)
Plasma alkaline phosphatase isozyme in Iraqi fowl was studied by acrylamide gel electrophoresis. Two phenotypes fast and slow, were observed.These two phenotypes have been shown to be controlled by one single autosomal locus with two allel AKPF and AKPS. The gene frequency of AKPS is dominant over the AKPF. The result indicated that gene frequency of AKPF in leghorn and new hamshire was more frequent than in local Iraqi birds.Birds of fast isozyme type had higher 90 – day's egg production and egg weights as compared to those with slow isozyme. It is concluded that the fast isozyme can be used as gene marker for spotting out pullets with high body weight sexual maturity, high egg production and high egg weight.